The research of health education programme efficiency in changing the attitudes and behaviours of dental students in the field of oral health - Kalevski, Katarina; Gajić, Milica; Jevremović, Ana; Borotić, Nenad; Trifunović, Jovanka; Jovičić, Olivera; Milić, Jasmina; Vojinović, Jovan (Vojnosanitetski pregled, 2021)
Introduction/Aim. The interest in oral health quality and the tendency to evaluate, provide, improve and compare it, are constantly improving. The main aim of this research was to examine the effectiveness of health education programme to change habits, attitudes and behaviours of dental students. Methods. The research was conducted at the Faculty of Dentistry in Pančevo. The first stage was related to the survey, the measurement of oral health status and the implementation of targeted health education. The second stage was conducted after the health education intervention, as a survey of attitudinal and behavioural changes and clinical measurement of oral health change. The sample consisted of 65 first-year and 54 fourth-year students, a total of 119 students. The following were defined as research instruments: the research record, questionnaires [the original questionnaire, Hiroshima University Dental Behavioural Inventory (HU-DBI) questionnaire] and health education intervention for modelling factors that determine attitudes and behaviours related to oral health. The Decayed-missing-filled (DMF) index was used to evaluate oral health and hard dental tissue conditions. Results. At the beginning of the research we asked the students: “Do you think your mouth and teeth condition is good?” Contrary to our expectations, 15.4% of the first-year students and 37% of the fourth-year students did not know the answer, or thought they had a problem. 80% of the first-year and 85.2% of the fourth-year students had positive attitude about the statement that once in six months they should go to the dentist for a check-up. 7.7% of the first-year students did not remember the last time they had visited a dentist. The implemented health education intervention led, to some extent, to changes in habits, attitudes and behaviours of students related to oral health. Conclusions. Students of dental medicine do not have sufficiently clear attitudes and safe behaviour regarding oral health. Targeted health education intervention represents the method of choice to take care of one’s own health.